Animal Ethics: Beyond Neutrality, Universality, and Consistency (Bangladesh Journal of Bioethics, 2016)
This paper reflects a possibility of going beyond the postmodernists way of ethically examining non-human animals based on the tripartite pillars of neutrality, universality, and consistency. My concentration focuses on some interrelated queries, such as What does animal ethics conventionally mean? How did power, hierarchy, and domination separate humans from other animals? How does the fate of non-human animals (whether they ought to be morally considered or not) depend on humans moral values? How far is it justified to secure animal rights in the age of perilous animal use, especially for food or during animal experimentation? While examining these issues, I bring into light the several arguments and positions put forward by thinkers such as Jeremy Bentham, Peter Singer, Tom Regan, Carl Cohen, Brian Berry, and others. Moreover, my search is for a non-anthropocentric sustainable paradigm, to balance human interests and animal needs together, in order to sustain the future generations of human and non-human intimacy.